Implicit Measures Help Demonstrate the Value of Conservation Education in the Democratic Republic of the Congo - Bowie, Aleah; Krupenye, Christopher; Mbonzo, Pierrot; Minesi, Fanny; Hare, Brian (Frontiers in Psychology, 2020)
Biodiversity is being lost at unprecedented rates. Limited conservation resources must be prioritized strategically to maximize impact. Here we introduce novel methods to assess a small-scale conservation education program in the Democratic Republic of Congo. Lola ya Bonobo is the world’s only sanctuary for one of humans’ two closest living relatives, bonobos, orphaned by the illegal trade in bushmeat and exotic pets. The sanctuary is situated on the edge of the country’s capital, Kinshasa, its most densely populated region and a hub for the illegal wildlife trade that is imperiling bonobos and other endangered species. Lola ya Bonobo implements an education program specifically designed to combat this trade. Previous evaluation demonstrated the program’s efficacy in transmitting conservation knowledge to children. In Study 1, we use novel implicit tests to measure conservation attitudes before and after an educational visit and document a significant increase in children’s pro-conservation attitudes following direct exposure to bonobos and the education program. In Study 2, we show that adults exhibit high levels of conservation knowledge even before visiting the sanctuary, likely due to the sanctuary’s longstanding education efforts in Kinshasa. In Study 3, we explored adults’ empathetic attitudes towards bonobos before and after the sanctuary tour. Our results support the conservation education hypothesis that conservation education has improved relevant knowledge and attitudes in Kinshasa. Crucially, the present study validates new methods for implicitly assessing attitudes about environmental and social issues. These methods overcome typical biases in survey sampling and can be employed in diverse populations, including those with low literacy rates.